Conception, Fertilization and the Onset of Human Personhood: A Note on the Case Artavia Murillo et al. v. Costa Rica - Rivera López, Eduardo Enrique (2013)
In this critical note it is argued that one of the crucial arguments of the recent judgment by the Inter-American Court of Human Rights in Artavia Murillo fails and shows a common conceptual confusion in legal argumentation. The Court considers that the word “conception” in paragraph 4(1) of the American Convention on Human Rights must be understood as “implantation,” and not, as claimed by one part of the doctrine and the minority opinion in this case, as “ fertilization.” The normative consequence of this interpretation is that preimplantation embryos (for example, embryos in vitro) do not enjoy the legal protections established by the Convention, that is, the protection (in general) of a right to life. The main argument for this interpretation is that a preimplantation embryo is not viable unless it is implanted in the uterus. The argument is fallacious, since it attempts to support a normative conclusion on scientific, empirical premises alone.